Risk and safety in play : the law and practice for adventure playgrounds - Potter, Dave (E & FN Spon ; Distributed in the USA and Canada by Van Nostrand Reinhold, 1997)
Risk and Safety in Play draws on PLAYLINKS 35 years experience with adventure playgrounds and the findings in its three year development project 'Quality Play and Safety.' The text has been widely researched and commented on by playworkers.